Endogenous Lipogenic Regulators of Spore Balance in Aspergillus nidulans - Tsitsigiannis, Dimitrios I. (American Society for Microbiology, 2004)
The ability of fungi to produce both meiospores and mitospores has provided adaptive advantages in survival and dispersal of these organisms. Here we provide evidence of an endogenous mechanism that balances meiospore and mitospore production in the model filamentous fungus Aspergillus nidulans. We have discovered a putative dioxygenase, PpoC, that functions in association with a previously characterized dioxygenase, PpoA, to integrate fatty acid derived oxylipin and spore production. In contrast to PpoA, deletion of ppoC significantly increased meiospore production and decreased mitospore development. Examination of the PpoA and PpoC mutants indicate that this ratio control is associated with two apparent feedback loops. The first loop shows ppoC and ppoA expression is dependent upon, and regulates the expression of, nsdD and brlA, genes encoding transcription factors required for meiospore or mitospore production, respectively. The second loop suggests Ppo oxylipin products antagonistically signal the generation of Ppo substrates. These data support a case for a fungal “oxylipin signature-profile” indicative of relative sexual and asexual spore differentiation.